Impact of land loss on academic performance among rural adolescents in China: based on cognition-investment-performance framework - Hua, Jing; Li, Ruining (Frontiers in Environmental Science, 2023)
As an exclusive group resulting from land requisition and demolition during the process of urbanization, the education of children belonging to land-loss farming families has received worldwide attention. However, few studies have explored the mechanisms and effects of land loss on adolescents’ academic performance. Using 5,133 family samples in 2014 and 3,810 family samples in 2018 from China Family Panel Studies (CFPS), this study employed the PSM-DID and KHB models to explore the impact of land loss on the academic performance of rural adolescents. The findings indicate that compared to non-land-loss families, the academic performances of adolescents in the land-loss families were lower. Additionally, land-loss families have a lower awareness of educational value. This verifies the logical mechanism of “land loss→ family education cognition→ family human capital investment→ adolescents’ academic performance.” Gender differences exist in the negative effects of land loss on adolescents’ academic performance; land loss has a greater impact on boys. Therefore, the government should strengthen the training system for land-loss farmers, improve the social security system and state of female-led families, and focus on boys affected by land loss.